COST ACCOUNTING FOR MOTOR FREIGHT LINES. - Lehnberg, Val B. (The Accounting Review, 1950)
The accepted principles of cost accounting may be applied to the transportation of property by motor trucks in such manner that the cost of hauling each class will be determined. At the present time motor freight carriers, both common and contract, are required by governmental regulatory commissions to maintain uniform systems of accounts and to submit annual reports. While these accounts are very detailed with minute divisions and subdivisions of both revenue and expense, they do not reveal the cost of transporting property, because there is no method of apportioning or allocating the expenses to the particular service being rendered. The statement of profit and loss by classes is only tentative, because there are many other relevant factors to be considered. The percentages of load will vary. Also, the percentages of expenses to be assigned to the various classes will change. However, when a sufficient number of actual studies have been made to supply factual data, standard percentages can be determined. When these standard percentages are applied to expenses, the cost of transporting merchandise over a line haul can be established.